2020
DOI: 10.1371/journal.pone.0227513
|View full text |Cite|
|
Sign up to set email alerts
|

Filtered beauty in Oslo and Tokyo: A spatial frequency analysis of facial attractiveness

Abstract: Images of European female and male faces were digitally processed to generate spatial frequency (SF) filtered images containing only a narrow band of visual information within the Fourier spectrum. The original unfiltered images and four SF filtered images (low, mediumlow, medium-high and high) were then paired in trials that kept constant SF band and face gender and participants made a forced-choice decision about the more attractive among the two faces. In this way, we aimed at identifying those specific SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 110 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…This approach can examine the features that define facial impressions with minimal researcher bias 18 . In recent years, computer graphics (CG) modeling studies 19,20 , geometric morphometrics [21][22][23][24] , image statistics [25][26][27] , and deep learning methods have started being conducted 28,29 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can examine the features that define facial impressions with minimal researcher bias 18 . In recent years, computer graphics (CG) modeling studies 19,20 , geometric morphometrics [21][22][23][24] , image statistics [25][26][27] , and deep learning methods have started being conducted 28,29 .…”
mentioning
confidence: 99%
“…Furthermore, there is an asymmetric cap (like an asymmetric inverted U-shaped) relationship between body fat percentage and attractiveness 24 . In image statistics studies, Øvervoll et al 25 found that images processed with a high spatial frequency filter were preferred for female images, while images processed with a slightly lower spatial frequency filter were preferred for male images. Otaka et al 26 showed that skin appearance could be represented by two dimensions: pleasantness and glossiness.…”
mentioning
confidence: 99%
“…Imaging data also support similar findings (Bos et al, 2018; Glocker et al, 2009; Hahn et al, 2016). In general, these detailed features are more prevalent in relatively high SF faces than in low SF faces (Øvervoll et al, 2020; Vuilleumier et al, 2003). On the other hand, detailed information (relatively high SFs) is more suitable to help observers focus on cute objects with a local attention strategy and provide careful behavior.…”
Section: Discussionmentioning
confidence: 95%
“…The four SF bands, which spanned the most SF range, were selected respectively to correspond to low (SF1: 0.06∼0.55 cycles/degree), medium-low (SF2: 1.50∼2.50 cycles/degree), medium-high (SF3: 3.54∼5.55 cycles/degree), and high (SF4: 6.52 ∼ 10.55 cycles/degree) SFs. The range of four SFs was progressively increased, making the bandwidths equal on a log 10 scale (Øvervoll et al, 2020). The cycles/degree provides a retina-based SF image description.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation